Dosimetric impact of respiratory motion, interfraction baseline shifts, and anatomical changes in radiotherapy of non-small cell lung cancer. (October 2013) - Schmidt, Mai Lykkegaard; Hoffmann, Lone; Kandi, Maria; Møller, Ditte S.; Poulsen, Per Rugaard
Abstract Background. The survival rates for patients with non-small cell lung cancer (NSCLC) may be improved by dose escalation; however, margin reduction may be required in order to keep the toxicity at an acceptable level. In this study we have investigated the dosimetric impact of tumor motion and anatomical changes during intensity-modulated radiotherapy (IMRT) of patients with NSCLC. Material and methods. Sixteen NSCLC patients received IMRT with concomitant chemotherapy. The tumor and lymph node targets were delineated in the mid-ventilation phase of a planning 4DCT scan (CT1). Typically 66 Gy was delivered in 33 fractions using daily CBCT with bony anatomy match for patient setup. The daily baseline shifts of the mean tumor position relative to the spine were extracted from the CBCT scans. A second 4DCT scan (CT2) was acquired halfway through the treatment course and the respiratory tumor motion was extracted. The plan was recalculated on CT2 with and without inclusion of the respiratory tumor motion and baseline shifts in order to investigate the impact of tumor motion and anatomical changes on the tumor dose. Results. Respiratory tumor motion was largest in the cranio-caudal (CC) direction (range 0–13.1 mm). Tumor baseline shifts up to 18 mm (CC direction) and 24 mm (left-right and anterior-posterior) were observed. The average absolute difference in CTV mean dose to the primary tumor (CTV-t) between CT1 and CT2 was 1.28% (range 0.1–4.0%) without motion. Respiratory motion and baseline shifts lead to average absolute CTV-t mean dose changes of 0.46% (0–1.9%) and 0.65% (0.0–2.1%), respectively. For most patients, the changes in the CTV-t dose were caused by anatomical changes rather than internal target motion. Conclusion. Anatomical changes had larger impact on the target dose distribution than internal target motion. Adaptive radiotherapy could be used to achieve better target coverage throughout the treatment course.